PEMBANDINGAN SIMPANGAN DAN CAPACITY RATIO PADA PEMODELAN GEDUNG DENGAN DAN TANPA INITIAL SWAY IMPERFECTION - Retno Ajeng Zulia Octavia; Tri Widya Swastika (Politeknik Negeri Jakarta, 2020)
Initial Sway Imperfection is one of the stability requirements for structural steel design structure, as explained in SNI 1729-2015 the specification of steel building. It was also mentioned that initial sway imperfection can be simulated by giving notional load on the structure of steel building model which is 0,002 of the gravity load on each floor. However, consultants and practitioners never apply initial sway imperfection in the calculation of stability, even though it is very important in buckling prediction, especially in column section. This research was compared drift and capacity ratio in column section, with and without initial sway imperfection using 3D model of 7 floors building. The method that we used is DAM (Direct Analysis Method). In the first model without notional load and the second model by applying notional load. The results shows that the biggest drift value in the X direction increase from 0,2 mm to 135,2 mm, and in the Y direction increase from 0,1 mm to 55,4 mm, the capacity ratio increase from 0,04% to 16,73%. The drift value with initial sway imperfection exceeds the limits allowed by SNI 1726-2012, therefore it needs to enlarge column section. At the same time, the capacity ratio with initial sway imperfection is within the limit which is less than 1. Keywords: Initial Sway Imperfection, Notional Load, Deviation, Capacity Ratio.